Polymeric Nanoparticles as Oral and Intranasal Peptide Vaccine Delivery Systems: The Role of Shape and Conjugation - Prashamsa Koirala; Ahmed O. Shalash; Sung-Po R. Chen; Mohammad O. Faruck; Jingwen Wang; Waleed M. Hussein; Zeinab G. Khalil; Robert J. Capon; Michael J. Monteiro; Istvan Toth; Mariusz Skwarczynski (Vaccines, 2024)
Mucosal vaccines are highly attractive due to high patient compliance and their suitability for mass immunizations. However, all currently licensed mucosal vaccines are composed of attenuated/inactive whole microbes, which are associated with a variety of safety concerns. In contrast, modern subunit vaccines use minimal pathogenic components (antigens) that are safe but typically poorly immunogenic when delivered via mucosal administration. In this study, we demonstrated the utility of various functional polymer-based nanostructures as vaccine carriers. A Group A Streptococcus (GAS)-derived peptide antigen (PJ8) was selected in light of the recent global spread of invasive GAS infection. The vaccine candidates were prepared by either conjugation or physical mixing of PJ8 with rod-, sphere-, worm-, and tadpole-shaped polymeric nanoparticles. The roles of nanoparticle shape and antigen conjugation in vaccine immunogenicity were demonstrated through the comparison of three distinct immunization pathways (subcutaneous, intranasal, and oral). No additional adjuvant or carrier was required to induce bactericidal immune responses even upon oral vaccine administration.